1972
DOI: 10.1002/bjs.1800590114
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral double nipples

Abstract: procedure resulted in the rclief of symptoms in each casc but was not curative. Three patients survived for 8, 9, and 12 months, respectively, but then died with metastases. T w o patients are still alive 16 and 18 months, respectively, after operation, but I of these had hepatic metastases at the time of operation.Carcinoma of the duodenum should be considered in the differential diagnosis of all cases of obstructive jaundice. Careful radiological investigation is the most important diagnostic approach and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Carvajal (1972), in a study of 10,254 women in Venezuela, gives an incidence of 3.27%. Guest (cited by Brightmore 1972) in an examination of 20,000 school children in England gives an incidence of 0.4% with a 2:1 female to male ratio. The female to male ratio in Japan is 3:1, while in the Scandinavian and North American studies of SNN, male domination is reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvajal (1972), in a study of 10,254 women in Venezuela, gives an incidence of 3.27%. Guest (cited by Brightmore 1972) in an examination of 20,000 school children in England gives an incidence of 0.4% with a 2:1 female to male ratio. The female to male ratio in Japan is 3:1, while in the Scandinavian and North American studies of SNN, male domination is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Landauer (1939) suggested that SNN occur slightly more commonly on the left side. The single lesion is most common, but cases with two symmetrical lesions or multiple lesions have also been reported (Decholnoky 1939, Brightmore 1972. In the study of Carvajal (1952), 266 cases had a single lesion, 65 had two lesions, four individuals had three lesions and one person had four lesions.…”
Section: Fy>-mentioning
confidence: 99%
“…We believe the message to the practicing physician is that there is no need for radiographic or ultrasonographic investigation of the urinary tract in asymptomatic children found to have supernumerary nipples on routine physical examination. Supernumerary nipples (SNNs) have been described in correlation with a number of other abnormalities, including peptic ulcer, cardiovascular disease, vertebral malformations, neurosis, and migraine (1). Although the most encompassing works particularly stress an association between SNNs and kidney and urinary tract malformations (KUTMs) (2±8), other studies have failed to support this ®nding (9±15).…”
mentioning
confidence: 99%
“…Several ways to classify extra breast tissue have been proposed. Kajava (Brightmore 1972) found to be affected 2 @ Not affected @ Reported to be affected Fig. 1.…”
Section: Discussionmentioning
confidence: 97%